Comparison of OFDM System in terms of BER using Different Transform and Channel Coding - Pratima Manhas; M.K Soni (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
Orthogonal frequency division multiplexing is a type of multicarrier modulation technique which is used in wireless communication. OFDM can be used in various wireless and wired application such Digital audio broadcasting, digital video broadcasting & wireless LAN. The Performance of OFDM system depends on various parameters such as using different transform, different modulation and by putting various channel coding. In this paper OFDM system is modeled by using different transform (DWT/FFT), different modulation (BPSK, QPSK, QAM) and different channel coding (Linear / Cyclic block codes) for AWGN channel. The performance parameter is calculated as Bit error rate (BER) for various transform/modulation/channel coding based OFDM systems. MATLAB Simulink tool is used to calculate the bit error rate (BER).